Identification of mixed hardening parameters for aluminium sheet by cyclic loading tool - Ngoh, Rui Yong (2013)
This project is about identifying mixed hardening parameters of aluminium alloy AA 1100 by cyclic loading tool. The identified parameters are useful as input data in sheet metal forming simulation. It helps to improve the performance of the simulation to solve forming problem such as springback. The cyclic loading tools are fabricated to perform bending-unbending. Software Mastercam is used to generate G-code for advance machining on the fabrication process. The newly developed tool is installed on the tensile test machine for cyclic bending-unbending experiment. The experimental data acquired are converted into stress- strain data which are further analysis by using Matlab for parameters identification. The mixed hardening parameters for various thicknesses are obtained at the end of the project. R-square error are used to justify the accuracy of the parameters. The mixed hardening equation which is the combination of isotropic hardening law and kinematic hardening rule are fitting to the experimental data very well. Improvements in the newly developed tools are suggested to reduce friction and hence obtain better results.